Ni-625 Superalloy Foam Processed by Powder Space-Holder Technique - GÜLSOY, HAMİT ÖZKAN (SPRINGER, 2013)
In this work, porous Ni-625 superalloys were produced by use of a water soluble pore forming agent prior to sintering. Carbamide particles were used as the space-holder materials. After mixing and compaction, the space-holder particles were extracted using warm water leaching over a range of temperatures. The porous green parts were subsequently thermally debinding to remove the paraffin wax under a pure Argon atmosphere, and subsequently sintered at high vacuum. The effects of volume fraction of space-holder particles on density, porosity, and elastic modulus were investigated. Microstructures were captured using optical and scanning electron microscopy. Pore size was quantified using image analysis software integral to the scanning electron microscopy. In addition, compression tests were conducted on the sintered samples.
Keywords: metal foam; superalloys; sintering; STAINLESS-STEEL; AL-FOAMS; MECHANICAL-PROPERTIES; SINTERING PROCESS; MICROSTRUCTURE; PRECIPITATION; DISSOLUTION; TITANIUM; SHAPE